The Boron Nitride (B116n124) Fullerene: Stability and Electronic Properties from Dft Simulations - Cardenas-Jiron, G; Pino-Rios, R (Elsevier B.V., 2020)
The stability, electronic and optical properties of an isomer of B116N124 fullerene were analyzed by using the DFT calculations. The results indicate that the structure is stable and exhibits a high cohesion energy (Ecoh = −7.82 eV/atom). The quantum descriptors of this fullerene revealed: low values for polarity, chemical reactivity and work function, as well as electronic behavior like conductor. According to above features, this system can be considered in electrical, electronic or biological applications. This cluster presents its highest absorption peak around 244–281 nm and it was characterized through the natural transition orbitals showing a π → π* behavior. © 2020 Elsevier B.V.